LOCAL CULTURE EXPERIENCE AND NOVELTY SEEKING: A COMPARISON ON ISTANBUL AND ANTALYA TOURISM DESTINATIONS - Sahin, Ilker; Guzel, F Ozlem (PEOPLE: International Journal of Social Sciences, 2018)
Distinguishing the society from others, cultural assets create a unique local culture experience for tourists and lead to satisfaction by influencing the novelty seeking motivation. Based on this hypothesis, the aims of this research are as follows; a) to examine the effect of the local cultural experience on novelty seeking behavior, b) to examine the influence of the local culture experience on tourist satisfaction, and c) to assess the mediating role of novelty seeking between local cultural experience and satisfaction. Using structural equation modeling, a comparative study was carried out on Turkey's most-tourist attracting destinations which have distinctive DNA's in accordance with their specific positioning strategies. Findings revealed that local culture experience, novelty seeking and tourist satisfaction variables are associated with each other in both destinations. The SEM suggests that the novelty seeking variable have the mediating role between local culture experience and satisfaction.